2019
DOI: 10.1523/jneurosci.2798-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Memory Reactivation during Sleep Elicits Neural Signals Related to Learning Content

Abstract: Retrieval of learning-related neural activity patterns is thought to drive memory stabilization. However, finding reliable, noninvasive, content-specific indicators of memory retrieval remains a central challenge. Here, we attempted to decode the content of retrieved memories in the EEG during sleep. During encoding, male and female human subjects learned to associate spatial locations of visual objects with left-or right-hand movements, and each object was accompanied by an inherently related sound. During su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
58
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 36 publications
11
58
0
Order By: Relevance
“…However, there is considerable variability in signal characteristics across SOs and spindles (e.g., event durations or peak times), and such across-event variability diminishes classification power which relies on spatiotemporal activation patterns common across events. That said, decoding levels observed here are in line with previous TMR studies examining sleep-related memory reactivation with multivariate classification 36 , 53 , 57 . Importantly, we found that higher decoding performance correlates with the behavioral expression of memory consolidation across participants, further corroborating the functional significance of reactivation.…”
Section: Discussionsupporting
confidence: 91%
“…However, there is considerable variability in signal characteristics across SOs and spindles (e.g., event durations or peak times), and such across-event variability diminishes classification power which relies on spatiotemporal activation patterns common across events. That said, decoding levels observed here are in line with previous TMR studies examining sleep-related memory reactivation with multivariate classification 36 , 53 , 57 . Importantly, we found that higher decoding performance correlates with the behavioral expression of memory consolidation across participants, further corroborating the functional significance of reactivation.…”
Section: Discussionsupporting
confidence: 91%
“…Given the simplicity of the contrastive loss formula, it is not hard to imagine that it could be implemented by a real neural circuit driving plasticity based on both similarity and differentiation ( 67 ). Conceptually, this neural learning circuit would complement the neural system to be learned (e.g., the ventral pathway), computing and relaying errors back to the system as learning occurs, either rapidly in real time ( 68 ) or possibly with delayed batching as part of memory consolidation ( 69 ). Following up on these possibilities will require the detailed comparison of real-time empirical representation changes during learning ( 67 , 68 ) to fine-scale model updates during training.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar approach, cued responses that successfully elicited sleep spindles also predicted the quality of later memory retrieval. Furthermore, the greater the associated sigma power increase, the better was the later performance (630). Cueing was also successfully used to probe potential different roles in SO-spindle coupling during N2 and N3 sleep in humans (241).…”
Section: Targeted Memory Reactivation Involving Sleep Spindlesmentioning
confidence: 99%